Molo’opu Tradition in Terms of Gorontalo’s Etnhic Leadership - Rahmawati, Rahmawati; Yahiji, Kasim (Madania: Jurnal Kajian Keislaman, 2021)
This paper aimed to study about acculturation between religion and Molo’opu customs (adat) in Gorontalo society and to describe leadership philosophical meaning. This is descriptive qualitative research. Data collection techniques used during the study process were participant observation, guided interviews, and documentation. It applied anthropological, sociological, and historical approaches. The results showed that the implementation of Molo’opu tradition  is based on the philosophy of “Adati hula hula’a to syaraa, syaraa hula-hulaa tokitabi” which means that adat based on syara’ and syara’ based on the Quran are hereditary-philosophical base in all dimensions of the Gorontalo people. The acculturation between the sharia commandments and the preservation of the Molo'opu tradition is reflected in the traditional apparatus and processions as well as the chanting of Tuja'i poetry containing moral values that can motivate leaders to have a deep awareness that they are as a substitute for Allah and His Messenger to lead this world to the right path. Moral values of Molo’opu are: 1). Mo’odelo “Mo’oiyoto Allah, wo lo Nabi Mursalah lo Waliu sagala” 2).Mo’olindapo 3) Dulohupa 4) Huyula 5) Balata Yipilo 6) Ponuwo dan Loyode. The implementation of the Molo'opu is essentially a traditional welcome and respect, as well as the implementation of civilized humanity. The sacred values contained in the Molo'opu tradition will inspire newly appointed leaders to carry out the mandate as a responsibility to Allah Swt.  Tulisan ini bertujuan mengkaji akulturasi antara agama dan adat Molo’opu pada masyarakat Gorontalo dan mendeskripsikan makna filosofi kepemimpinan dalam pelaksanan tradisi molo’opu. Jenis penelitian ini adalah kualitatif deskriptif dengan tehnik pengumpulan data melalui observasi yang berpartisipasi, wawancara terpimpin, dan dokumentasi.  Pendekatan yang diterapkan selama penelitian antara lain pendekatan antropologi, sosiologi, dan historis. Hasil penelitian ini menunjukkan bahwa pelaksanaan tradisi Molo’opu berdasar pada filosofi “Adati hula hula’a to syaraa, syaraa hula-hulaa tokitabi” yang artinya adat bersendikan syara’ dan syara’ bersendikan kitabullah, merupakan filosofi yang ditaati secara turun temurun pada semua dimensi kehidupan masyarakat Gorontalo. Akulturasi antara perintah syariat dan pelestarian tradisi Molo’opu tercermin dalam perangkat adat dan prosesi serta lantunan syair Tuja’i yang mengandung pesan moral yang dapat memotivasi para pemimpin bahwa dirinya adalah penggati Allah dan Rasul-Nya. Pesan moral Molo’opu antara lain: 1). Mo’odelo “Mo’oiyoto Allah, wo lo Nabi Mursalah lo Waliu sagala ” 2).Mo’olindapo 3) Dulohupa 4) Huyula 5) Balata Yipilo  6) Ponuwo dan Loyode. Pada hakekatnya pelaksanaan tradisi Molo’opu adalah penyambutan dan penghormatan secara adat, dan implementasi kemanusiaan yang beradab. Nilai sakral yang terkandung dalam tradisi Molo’pu ini yang akan mengilhami pemimpin yang baru dilantik untuk melaksanakan amanah yang diembannya dengan penuh rasa tanggung jawab kepada Allah Swt.